The Implementation of Moving Class as a Method of Socialization for New Student Admissions - Dariyanto Dariyanto; Muhamad Ibnu Sholeh; Fitri Amalia Majid; Binti Mar’atus Sholihah (Seutia Hukamaa Cendekia, 2025)
This research explores the socialization of New Student Admissions at the high school level, which often occurs in a one-way, information-rich, and dialogue-deficient manner. This approach can lead to procedural misconceptions and reduced student engagement. The study aims to clarify the use of moving classes as a socialization method for PMB at SMAN Plosoklaten, identify necessary information and student segmentation, and develop a sustainable implementation model. Using a descriptive qualitative approach with a field study design, the research involves teachers, grade XII students, and selected university representatives. Data collection includes observation, in-depth interviews, and documentation, analyzed through an interactive model involving data reduction, presentation, and conclusion formulation. Findings show that moving classes enhances student participation and comprehension by organizing socialization through thematic stations, which facilitate movement, discussion, simulation, and Q&A sessions in small groups. Recommended stations include introductory programs, selection pathways, fees, scholarships, lecture simulations, and consultations. The study emphasizes the segmented information needs of students, particularly in study program interests, scholarships, financing, selection procedures, and career prospects, necessitating differentiated visit routes and consulting services. Implications include managerial prerequisites such as infrastructure readiness, scheduling, facilitator development, technology integration, feedback-driven evaluation, and collaboration among parents, colleges, and universities, ensuring consistent and sustainable model implementation. These findings expand moving classes beyond formal learning to educational transition, reducing administrative errors and enhancing students' information literacy before higher education enrollment.